Revision of the Griburius posticatus (Suffrian, 1866) species group (Coleoptera: Chrysomelidae: Cryptocephalinae) - Sassi, Davide (Zootaxa, 2024)
Nine species of Griburius Haldeman, 1849 have been revised and critically discussed. One additional species, formerly included in Metallactus Suffrian, 1852, has been transferred to Griburius: Griburius tredecimpunctatus (Suffrian, 1866) comb. nov. The following synonymies are proposed: Griburius hyacinthinus (Erichson, 1848) (= Griburius fragrans (Suffrian, 1866) syn nov.), Griburius posticatus (Suffrian, 1866) (= Griburius distigma (Suffrian, 1866) syn nov.; = Griburius rufomarginatus (Suffrian, 1866) syn nov.), Griburius tredecimpunctatus (Suffrian, 1866) comb. nov. (= Griburius incomparabilis (Suffrian, 1866) syn. nov.). Type series of each species were tracked down and a lectotype was designated for each of them, respectively. Redescriptions, illustrations and current known distribution of all the treated species are given. Additionally, Griburius bicoloratus sp. nov. and Griburius consanguineus sp. nov., both from Brazil, are described as new to science.